Distinctive Immunomodulatory and Inflammatory Properties of the Escherichia coli Type II Heat-Labile Enterotoxin LT-IIa and Its B Pentamer following Intradermal Administration - Mathias-Santos, Camila (American Society for Microbiology, 2011)
The type I and type II heat-labile enterotoxins (LT-I and LT-II) are strong mucosal adjuvants when they are coadministered with soluble antigens. Nonetheless, data on the parenteral adjuvant activities of LT-II are still limited. Particularly, no previous study has evaluated the adjuvant effects and induced inflammatory reactions of LT-II holotoxins or their B pentameric subunits after delivery via the intradermal (i.d.) route to mice. In the present report, the adjuvant and local skin inflammatory effects of LT-IIa and its B subunit pentamer (LT-IIaB(5)) were determined. When coadministered with ovalbumin (OVA), LT-IIa and, to a lesser extent, LT-IIaB(5) exhibited serum IgG adjuvant effects. In addition, LT-IIa but not LT-IIaB(5) induced T cell-specific anti-OVA responses, particularly in respect to induction of antigen-specific cytotoxic CD8(+) T cell responses. LT-IIa and LT-IIaB(5) induced differential tissue permeability and local inflammatory reactions after i.d. injection. Of particular interest was the reduced or complete lack of local reactions, such as edema and tissue induration, in mice i.d. inoculated with LT-IIa and LT-IIaB(5,) respectively, compared with mice immunized with LT-I. In conclusion, the present results show that LT-IIa and, to a lesser extent, LT-IIaB(5) exert adjuvant effects when they are delivered via the i.d. route. In addition, the low inflammatory effects of LT-IIa and LT-IIaB(5) in comparison to those of LT-I support the usefulness of LT-IIa and LT-IIaB(5) as parenterally delivered vaccine adjuvants.